Anaerobic degradation of palm oil mill effluent with aluminum bauxite residue for methane production. Issue 2 (March 2021) - Ahmad, Anwar; AlDawey, Salam S; Reddy, SS
Experimental study of the anaerobic digestion of palm oil mill effluent (POME) was carried out in an anaerobic upflow sludge blanket reactor (UASBR) with bauxite residue. The production rate of methane 114 L/gCOD/d and CH4 concentration was 205 L gCOD/d at 8.5 g/L of bauxite residue in UASBR. The results showed that the highest methane yield was 37.5 L gCODadded /h; CO2 reduction 1.5 L gCODadded and chemical oxygen demand (COD) removal reached 98.3% at 8.5 g/L of bauxite residue, respectively. The results the best by the modified kinetic model and Umax was 100 mg/L. The kinetic of methane production was also studied. The methane yield coefficient, YM, was 0.69 L CH4 /gCODremoved . Anaerobic digestion of acetate was the dominant soluble metabolites in development and specific methanogenic activity results showed that high observed between stoichiometric and experimental higher methane production.